PREFERENSI WISATAWAN TERHADAP OBJEK WISATA DI SEKSI PENGELOLAAN TAMAN NASIONAL I CEMORO LAWANG TAMAN NASIONAL BROMO TENGGER SEMERU - , LAKSMI SEKAR W, Kaharuddin, S.Hut, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bromo Tengger Semeru National Park has many attractions, but the attractions are visited by many tourists confined to the attraction of Mount Bromo, Laut Pasir, and Penanjakan located in National Park Management Section I Cemoro Lawang. The condition raises the question of what factors are causing travelers prefer third of the attraction. This study aims to determine the factors that influence the preference of tourists in attractions of Mount Bromo, Laut Pasir, and Penanjakan, also determine the relationship between the characteristics of travelers with tourist preference in attraction and Mount Bromo, Laut Pasir, and Penanjakan attraction. This study is conducted in May 2013 and February 2014 with survey as the research method and questionnaire as the instrument. The questionnaires are distributed using accidental sampling, which involved 99 domestic tourists and 92 foreign tourists. The analysis used to measure the factors that affect travelers preference using Fishbein multiatribut analysis, while to analyze the relationship between the characteristics of travelers with tourist preference using Chi-square analysis. The factors which influence their tourism preference in Mount Bromo, the Laut Pasir and Penanjakan of Bromo Tengger Semeru National Park are their uniqueness, coolness, and beauty. Besides, Mount Bromo dan Laut Pasir have higher level of preference than that of Penanjakan tourism objects. Preference in the attraction of foreign tourists in Mount Bromo and Laut Pasir is influenced by the level of education and type of work, while the preference of foreign tourists in Penanjakan attraction is influenced by age and type of work.